ANALISIS POTENSI KETERSEDIAAN DAN PEMASARAN BAMBU BELANGKE (Gigantochloa pruriens Widjaja) DI HUTAN RAKYAT BAMBU DESA TIMBANG LAWAN KECAMATAN BAHOROK KABUPATEN LANGKAT DALAM INDUSTRI DUPA BAMBU - Ridho Alamsyah; Oding Afandi; Ridwanti Batubara (Program studi Kehutanan USU, 2013)
In the rural communities living in Indonesia, bamboo plays a very important contribution, but unfortunately the awareness of the importance of bamboo is still low for rural communities in general. This study aims to determine the potential availability and marketing of bamboo Belangke (Gigantochloa Widjaja pruriens) at Timbang Lawan Village, Sub-District of Bahorok, District of Langkat as raw material for bamboo incense. The method used in this study is an inventory and interview the owners of bamboo forests and bamboo incense marketing actors. The results of this study indicate that there are approximately 8.16 ha of bamboo forest species Belangke (G. pruriens Widjaja), with the potential rods that can be used for making incense sticks bamboo is 33,020 bamboos. Marketing system in the production of bamboo incense industries include bamboo processing, first seller, processors, seller, and consumers, with their respective profit margins ranging from bamboo to the merchant processor was 43%, 22.7%, 49%, and 58% . While the yield resulting from any processed bamboo rod with a size of 43 cm, 48 cm, 60 cm, and 65 cm were 90.34%, 86.50%, 84.92%, and 85.86%. Keywords: Belangke Bamboo, Bamboo Potention, Stock and Marketing, Bamboo Incense, Timbang Lawan Village